The Effect of Different Starter Dosage to Organoleptic Value of Kefir Cow Milk Products - Ardini, Tivani; Nurmiati, Nurmiati; Periadnadi, Periadnadi (Advances in Tropical Biodiversity and Environmental Sciences; Vol 2 No 1 (2018): ATBES, 2018)
The study of "The Effect of Different Starter Dosage to Organoleptic Value of Kefir Cow Milk Products" was carried out from May to July 2016 at the Microbiology Research Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Andalas University, Padang. The purpose of this study was to determine the organoleptic value (aroma, taste and organoleptic) of cow's milk kefir products from three different starter doses, and the results were with Wilcoxon Level Test. The results showed that organoleptic assessment of the aroma of cow milk kefir products with a treatment dose of 15% starter (3.00) was the most preferred dose for the panelist, while kefir with a treatment dose of 5% (2.27) is a dose that is less preferred by panelists. The taste assessment of the organoleptic of cow's milk kefir products, the starter dose of 10% (2.87) was the most preferred by the panelists, but the dose of 15% (2.33) was the least. Similar to the taste, the consistency of cow milk kefir with the dose of 10% (3.07) was most preferred, while the dose of 15% (2.33) was least preferred by the panelists .